Workshop Optimalisasi Literasi Calistung Untuk Pendidik Anak Usia Dini di Gugus Paud III Kecamatan Kertak Hanyar - Kamariah, Kamariah; Haswinda Harpriyanti; M. Saufi (Jurnal Pengabdian, 2025)
The workshop "Optimization of Literacy and Numeracy for Early Childhood Educators in PAUD III Cluster, Kertak Hanyar Sub-district" aims to enhance educators' ability to teach literacy and numeracy (reading, writing, and arithmetic), which are fundamental for children's cognitive development. Optimal early literacy can improve children's ability to absorb knowledge and support their future academic success. Through this training, educators are empowered to use effective, enjoyable methods that align with children's developmental stages, which will positively impact the quality of education in the area. The community service method includes socialization and needs identification with educators, interactive workshops focusing on teaching literacy and numeracy using fun methods such as games and songs, as well as simulations and hands-on practice. The creation of locally-based learning modules is also undertaken to support classroom implementation. Furthermore, evaluation and mentoring are carried out to ensure the sustainability and effectiveness of the training. The results of the activity show that the locally-based approach has a positive impact on both teachers and students. Teachers gain creative teaching methods, while students show increased interest in learning. Participants are also introduced to the integration of local culture into learning, the creation of simple teaching media, and the teaching of literacy through traditional stories and games, all aimed at improving the quality of teaching in early childhood education.